Fostering Emotional and Moral Development in Islamic Boarding Schools: The Impact of Talaqqȋ and Halaqa Traditions - Ismail, Sulaiman; Sabri, Hatta; Asari, Hasan; Yamin, Martinis; Yunus, Marzudi Muhammad (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2024)
The article scrutinizes the teacher-student respected relationship within the talaqqȋ and ḥalaqa traditions of Salafis Boarding Schools. The purpose of the study is to explore the psychological dimensions of this relationship, specifically recognized in Acehnese society as “Ta'zhim keu Guree” (respect to the teacher) as the main âdâb (virtues) within this bond, focusing on the principle of respect. This study employed a participatory action research methodology, using in-depth interviews and participant observation as the primary research instruments, conducted at the Dayah Nurul Hikam Al-Waliyah in Kota Langsa, Aceh Province. The study found that the teacher-student relationship within the talaqqȋ and ḥalaqa tradition acts as a dynamic channel for fostering emotional well-being and psychological growth among students. The respectful bond emerging from this relationship nurtures well-rounded individuals committed to intellectual and moral growth. Ẩdâb, as an Islamic cornerstone, epitomizes respect, humility, and gratitude, bolstering emotional well-being and ethics. The findings suggest that these traditions can be a valuable model for educational institutions aiming to promote emotional well-being, psychological growth, moral ethics, and alignment with Islamic teachings. Additionally, âdâb is highlighted as a valuable tool for promoting positive social change in communities.